Enhancing Informatics Teacher Training with Interactive Mobile Case Technologies - Akhitova, Riza; Alzhanov, Aitugan; Borisov, Vitaliy (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The study explores the use of case-based methods to enhance the professional competencies of future computer science teachers, focusing on communication, creativity, and problem solving skills. Conducted at L.N. Gumilyov Eurasian National University, the research involved instructors and students in collaborative activities to evaluate these skills. The findings indicate that while communicative and creative approaches were commonly applied, interpersonal conflicts often emerged during problem solving exercises. Most participants emphasized the critical role of effective communication in succeeding within modern educational settings. The study underscores the potential of case-based technologies to develop essential teaching skills and adapt to the demands of contemporary education. The conclusions suggest strategies for improving teacher training, advancing adaptive pedagogy, and leveraging technology to transform education. These insights contribute to the broader academic discussion on incorporating innovative methods into teacher education, with implications for institutional policies and community advancement.